2020
DOI: 10.37190/abb-01502-2019-02
|View full text |Cite
|
Sign up to set email alerts
|

Absolute and relative reliability of several measures of static postural stability calculated using a GYKO inertial sensor system

Abstract: Purpose: The aim of this study was to analyse absolute and relative reliability of a number of postural static stability measures obtained from a GYKO inertial sensor system in young adults. Methods: The study examined 29 healthy non-athlete young adults. A test was performed for 30 s while standing on one foot, without moving, with eyes open and arms relaxed along the sides of the body. The examinations were performed twice, with a one-week interval. Relative reliability was measured using the intraclass corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…overall, the total balance score reliability appears similar to other smartphone applications; Amick et al [14] report excellent relative reliability with Iccs of 0.78 (SEM: 5.82) in standing tasks (full contact with the floor, double or single leg standing, 2 trials) using the Sway balance mobile application. Good to excellent relative reliability Icc indices are also reported for postural stability assessments with accelerometers (Icc: 0.62-0.71 [10], Icc: 0.736-0.972 [12]).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…overall, the total balance score reliability appears similar to other smartphone applications; Amick et al [14] report excellent relative reliability with Iccs of 0.78 (SEM: 5.82) in standing tasks (full contact with the floor, double or single leg standing, 2 trials) using the Sway balance mobile application. Good to excellent relative reliability Icc indices are also reported for postural stability assessments with accelerometers (Icc: 0.62-0.71 [10], Icc: 0.736-0.972 [12]).…”
Section: Discussionmentioning
confidence: 90%
“…overall, taken an adequate number of trials, the results encourage the use of a smartphone application for testing standing postural stability in ballet dancers. this approach employs a low-cost and of high-portability tool for field assessment compared with expensive and of limited-portability laboratory equipment such as the force plate gold standard [2,7,26], accelerometers [3,7,[10][11][12], or a motion capture system [6,8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It determines three main measures of body sway: sway length and area, sway travel speed and sway frequency. Recent study by Jaworski et al 74 showed moderate to good relative reliability scores for all the postural stability measures, with ICC values ranging from 0.62 to 0.70. For most of the analysed variables, SEM% ranged from ~10% to 14%.…”
Section: Methods and Analysismentioning
confidence: 92%
“…A physical ability detection system (GYKO; Microgate) 26,27 will be used. This system contains a highspeed 3D accelerometer and gyroscope to capture data on 4 aspects: (1) walking and running, where the rocking levels of the torso during walking and running are compared; (2) posture, where the ability of the torso to maintain stability and balance when standing still is monitored;…”
Section: Gykomentioning
confidence: 99%